Macroscopic and anatomical investigation of interlocked grain in Acacia mangium - Ogata, Y.; Fujita, M.; Nobuchi, T.; Sahri, M.H. (International Association of Wood Anatomists, 2003)
Interlocked grains record change in the orientation of axial elements. In this report, vessel and fiber orientations in Acacia mangium Willd. were compared macroscopically and microscopically to analyze the interlocked grain. A method to print the cylindrical surface of a dry wood disk after bark exfoliation was devised to evaluate the stem axis and circumferential grain fluctuation and revealed circumferential heterogeneity in the vessel orientation. Fiber orientation manifested on some radial splits also was heterogeneous. A 3 mm-thick transverse plate was used to estimate vessel orientation with soft X-ray photography, which enables a wider-ranging evaluation than microscopy. Serial tangential thin plates and sections were used to measure fiber orientation angle with reflecting and polarized light microscopy, respectively, and fast Fourier transform. Both vessel and fiber orientations had a similar radial tendency and distinct inversion of the grain. However, the vessel orientation had a larger amplitude of change than fiber orientation.